Soul by soul : life inside the antebellum slave market - Johnson, Walter, 1967- (ACLS Humanities E-Book., 1999)
"Soul by Soul tells the story of slavery in antebellum America by moving away from the cotton plantations to the heart of the domestic slave trade. Taking us inside the New Orleans slave market, the largest in the nation, where 100,000 men, women, and children were packaged, priced, and sold, Walter Johnson transforms the statistics of these chilling transactions into the human drama of traders, buyers, and slaves, negotiating sales that would alter the life of each. What emerges is not only the brutal economics of trading but the vast and surprising interdependencies among the actors involved."--Jacket.